2022
DOI: 10.1016/j.afjem.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and reliability of smartphone captured radiologic images communicated via WhatsApp®

Abstract: Introduction Sending radiographic images as instant messages have become a common means of communication between physicians, aiding in triaging and transfer decision-making in emergencies. While use of technology is increasing, this is not the case for the underserved or rural areas of South Africa with no picture archiving and communications system or advanced hardware in place. In these areas, the medical staffing population have nearly universal access to smartphones and could benefit from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…WhatsApp can offer a cost-effective, user-friendly, and efficient communication option in neurosurgical practice [ 4 , 5 ]. It proved to be useful for professional communication in different medical disciplines such as ophthalmology [ 6 ], emergency medicine [ 7 ], radiology [ 8 ], dermatology [ 9 ], orthopedics [ 10 ], pathology [ 11 ], and burn care [ 12 ]. WhatsApp facilitates physician-physician communication [ 13 ], improves medical care [ 14 ], and enhances decision-making [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…WhatsApp can offer a cost-effective, user-friendly, and efficient communication option in neurosurgical practice [ 4 , 5 ]. It proved to be useful for professional communication in different medical disciplines such as ophthalmology [ 6 ], emergency medicine [ 7 ], radiology [ 8 ], dermatology [ 9 ], orthopedics [ 10 ], pathology [ 11 ], and burn care [ 12 ]. WhatsApp facilitates physician-physician communication [ 13 ], improves medical care [ 14 ], and enhances decision-making [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advent of smartphones coupled with high-speed internet has broken new frontiers in human connectivity and the way we disseminate and acquire information, especially in the fast-paced medical field. Digitized radiological images are conveniently transmitted from one location to another, even around the globe, within seconds on a regular basis for the purpose of consultation, timely diagnosis and patient management (Kotalwar et al., 2021; Ntja et al., 2022; Stahl et al., 2017; Westberg et al., 2017). In a highly imaging-dependent orthopaedic speciality, timely and accurate plain radiograph interpretation is paramount to supplement the history and physical examination findings in order to reach a diagnosis and deliver appropriate patient management (Giordano et al., 2015; Gulacti et al., 2016; Naqvi et al., 2014; Stahl et al., 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, smartphone penetration has significantly increased, especially in LMICs, with over 90% ownership and around 50% mobile internet connectivity 3 . This presents new opportunities for the quick and easy sharing of radiographic images to aid clinical decision-making 4 . Studies have shown that smartphone-captured radiographic images, communicated through messaging applications like WhatsApp, demonstrate similar diagnostic accuracy compared to viewing images on full-featured PACS systems 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This presents new opportunities for the quick and easy sharing of radiographic images to aid clinical decision-making 4 . Studies have shown that smartphone-captured radiographic images, communicated through messaging applications like WhatsApp, demonstrate similar diagnostic accuracy compared to viewing images on full-featured PACS systems 4 . In these approaches, a CXR image captured via smartphone or digital camera is transmitted to radiologists for remote review and diagnosis.…”
Section: Introductionmentioning
confidence: 99%